2019
DOI: 10.3892/etm.2019.7226
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA‑130a regulated by HPV18 E6 promotes proliferation and invasion of cervical cancer cells by targeting TIMP2

Abstract: Human papillomaviruses (HPVs) have important roles in the development and progression of cervical cancer, but the underlying mechanisms are yet to be fully elucidated. MicroRNA-130a (miR-130a) has previously been reported to promote cervical cancer growth. However, the underlying molecular mechanisms by which miR-130a promotes cervical cancer progression have remained largely elusive. In the present study, polymerase chain reaction and western blot analyses were performed to examine the expression levels of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…To date, the role of miR-130a in the progression of CC carcinogenesis is not completely understood. Yin et al ( 40 ) reported that high expression of miR-130a was significantly associated with lymph node metastasis and an advanced clinical stage of CC. The results of the present study indicated that the expression of miR-130a in CC tissues was obviously higher compared with healthy cervical tissues, and miR-130a knockdown inhibited CC cell proliferation and invasion in vitro and in vivo compared with miR-130ai NC and control antagomiR, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the role of miR-130a in the progression of CC carcinogenesis is not completely understood. Yin et al ( 40 ) reported that high expression of miR-130a was significantly associated with lymph node metastasis and an advanced clinical stage of CC. The results of the present study indicated that the expression of miR-130a in CC tissues was obviously higher compared with healthy cervical tissues, and miR-130a knockdown inhibited CC cell proliferation and invasion in vitro and in vivo compared with miR-130ai NC and control antagomiR, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…a previous study demonstrated that the mir-130 family (mir-130b, mir-301a and mir-301b) promoted the migration and invasion of bladder cancer cells via negative regulation of phosphatase and tensin homolog (PTen) (18). Jiang et al (29) revealed that mir-130a promoted the proliferation, migration and invasion of gastric cancer cells via targeting runX3, and Yin et al (28) verified that miR-130a enhanced the proliferation and invasion of cc cells via modulating TiMP2. in accordance with the results of these previous studies, in the present study it was concluded that the upregulation of mir-130a-3p contributed to the progression of cc.…”
Section: Discussionmentioning
confidence: 99%
“…chen et al (27) reported that upregulation of mir-130a expression was associated with the TnM stage and lymph node metastasis of colorectal cancer. Yin et al (28) demonstrated that upregulation of miR-130a was significantly associated with lymph node metastasis and an advanced clinical stage of cc. consistent with these previous studies, the present study demonstrated that high expression of mir-130a-3p was significantly associated with the FiGo stage, lymph node metastasis and depth of cervical invasion in patients with cc.…”
Section: Discussionmentioning
confidence: 99%
“…mir-130a has been reported to promote cancer growth (16). Yin et al (17) reported that the upregulation of mir-130a was highly correlated with advanced clinical stage and lymph node metastasis in cervical cancer. Therefore, inhibition of mir-130a expression may represent a treatment strategy with potentially antileukemic effects.…”
Section: Introductionmentioning
confidence: 99%